2007
DOI: 10.1152/jn.00178.2007
|View full text |Cite
|
Sign up to set email alerts
|

Decoding a New Neural–Machine Interface for Control of Artificial Limbs

Abstract: An analysis of the motor control information content made available with a neural-machine interface (NMI) in four subjects is presented in this study. We have developed a novel NMI-called targeted muscle reinnervation (TMR)-to improve the function of artificial arms for amputees. TMR involves transferring the residual amputated nerves to nonfunctional muscles in amputees. The reinnervated muscles act as biological amplifiers of motor commands in the amputated nerves and the surface electromyogram (EMG) can be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
167
1
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 192 publications
(178 citation statements)
references
References 22 publications
8
167
1
2
Order By: Relevance
“…For example, using classic EMG features, a classification accuracy of 98% and 93% was previously reported for two patients and 8 classes 30 , which is a similar result as obtained in the present study for patients T1 and T2 for 7 and 9 classes, respectively. In our experiment, however, the performance with classic EMG features degraded for patient T3 when classifying 11 classes and was lower than that previously reported in four patients for 16 classes 19 . However, three of the four patients in this previous study were transhumeral amputees with physiological innervation of the lateral heads of biceps and triceps and the window duration used for the analysis (256 ms) was longer than in our study (100 ms).…”
Section: Methodscontrasting
confidence: 99%
See 3 more Smart Citations
“…For example, using classic EMG features, a classification accuracy of 98% and 93% was previously reported for two patients and 8 classes 30 , which is a similar result as obtained in the present study for patients T1 and T2 for 7 and 9 classes, respectively. In our experiment, however, the performance with classic EMG features degraded for patient T3 when classifying 11 classes and was lower than that previously reported in four patients for 16 classes 19 . However, three of the four patients in this previous study were transhumeral amputees with physiological innervation of the lateral heads of biceps and triceps and the window duration used for the analysis (256 ms) was longer than in our study (100 ms).…”
Section: Methodscontrasting
confidence: 99%
“…The classification results indicated an almost perfect discrimination (on average >97%) of up to 11 classes. The results obtained from global EMG analysis in this study are partly in agreement with those reported in previous studies (e.g., 15,19,30 ). However, given the relatively small number of available TMR patients in the current and previous studies and differences in the experimental and analysis conditions, comparisons between studies are difficult.…”
Section: Methodssupporting
confidence: 93%
See 2 more Smart Citations
“…Para la identificación de diferentes tipos o intenciones de movimiento se utilizó un clasificador lineal basado en análisis discriminante (LDA; linear discriminant analysis), al tratarse de una de las técnicas más utilizadas por su rapidez y que puede ser fácilmente implementado en un sistema real (Zhou et al, 2007).…”
Section: Clasificación Del Tipo De Movimientounclassified